Mild Cognitive Impairment: A Brief Review and Suggested Clinical Algorithm. (June 2014) - Ghosh, Sayantani; Libon, David; Lippa, Carol
Mild cognitive impairment (MCI) is a dynamic state between normal cognition and dementia, where interventions can be taken to stop or delay the progression to dementia. It is broadly of 2 types—amnestic, where memory loss is the chief concern and nonamnestic, where it is not. One variant of nonamnestic, dysexecutive, being more prevalent is sometimes known as a separate subtype by itself. Diagnosis of MCI is mostly clinical and is aided by various scales and neuropsychological testing. Functional imaging studies help in early detection and is superior to biomarkers or structural magnetic resonance imaging. Although there is no evidence supporting any pharmacological intervention, cognitive rehabilitation, memory training, and caregiver support play a strong role in limiting and sometimes reversing the ongoing cognitive decline. As the spectrum of MCI is heterogeneous, making the right diagnosis can be a challenging; hence, we need a systematic yet cost-effective algorithm for the timely management of MCI.